2004
DOI: 10.1124/jpet.104.078873
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor Growth, Angiogenesis, and Tumor Cell Proliferation by a Small Molecule Inhibitor of c-Jun N-terminal Kinase

Abstract: c-Jun N-terminal kinase (JNK) is a member of the mitogenactivated protein kinase family, and its function is critical for signal transduction in tumor and endothelial cells. JNK is a serine/threonine protein kinase that phosphorylates c-Jun, a component of the activator protein-1 transcription factor complex. We hypothesize that inhibiting JNK will lead to the inhibition of tumor growth; therefore, we evaluated the efficacy of the recently described JNK inhibitor SP600125 [anthra[1,9-cd] pyrazol-6 (2H)-one]. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 33 publications
5
56
0
Order By: Relevance
“…Whatever the case, it should be emphasized that activated JNK has positive and negative effects on urothelial carcinoma development. As to the role of JNK in tumor angiogenesis, Kim and colleagues 53 reported thrombospondin production can be mediated through JNK activation, whereas Ennis and colleagues 54 found JNK inhibition to suppress endothelial cell migration and development of vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the case, it should be emphasized that activated JNK has positive and negative effects on urothelial carcinoma development. As to the role of JNK in tumor angiogenesis, Kim and colleagues 53 reported thrombospondin production can be mediated through JNK activation, whereas Ennis and colleagues 54 found JNK inhibition to suppress endothelial cell migration and development of vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that the JNK inhibitor cause tumor regression in vivo (Ennis et al, 2005;Gururajan et al, 2005), we therefore assessed the combined anti-JunB/c-Jun strategy against melanoma cells in the C57BL/6 mice strain using conditions where the SP treatment alone had no significant effect. We observed a striking decrease in tumor size, apoptosis induction and a significant increase in the survival of mice inoculated with the JunB knockdown cells after the SP administration, demonstrating the enhanced potential therapeutics in vivo of the JNK inhibitor in cells lacking JunB.…”
Section: Discussionmentioning
confidence: 99%
“…This drug acts as a reversible ATP-competitive inhibitor of JNK, and has been shown to exhibit a selectivity of >20-fold relative to other tested kinases. Recent data show that SP inhibits cancer cell proliferation and tumor growth in mice (Ennis et al, 2005). Since increased c-Jun levels were associated with human melanomas (Choi et al, 2005;Lopez-Bergami et al, 2007) and based upon the fibroblast results described above, we reasoned that the effects of targeting c-Jun using SP in the melanoma-derived cell c-Jun/JunB inactivation induces apoptosis in cancer cells EN Gurzov et al line B16-F10 could be enhanced by additional silencing of JunB.…”
Section: Knockdown Of Junb Protein Increases C-jun Levels and The Promentioning
confidence: 99%
“…Whereas MEK1/2 inhibitors prevent VEGF-induced cell proliferation (Rousseau et al, 1997;Pedram et al, 1998), p38 MAPK inhibitors reportedly prevent VEGF-induced cytoskeletal re-organization and cell migration (Rousseau et al, 1997). The JNK pathway has also been linked to in vitro endothelial cell motility (Shin et al, 2001;Ennis et al, 2005) and proliferation (Ennis et al, 2005).…”
Section: Mkk Signaling and Tumor Vascularizationmentioning
confidence: 99%